THE REGULATION OF MORTGAGE SERVICING: LESSONS FROM THE FINANCIAL CRISIS. (20th December 2017) - McNulty, James E.; Garcia‐Feijoo, Luis; Viale, Ariel
Abstract : Pivotal litigation against the largest subprime mortgage servicer in the United States provides lessons about the appropriate regulation of mortgage servicing and adds to research about the causes of the financial crisis. Mortgage servicing is essential to the functioning of the financial system so servicers must be held to a high standard. The litigation revealed egregious practices but was settled quickly for a nominal amount and provided the servicer a very broad release of liability, allowing it to expand without correcting serious problems, and created significant wealth gains for the parent firm. Regulatory authority should not be split between agencies. ( JEL G28, G21, K40)